Use of Oncept melanoma vaccine in 69 canine oral malignant melanomas in the UK. (January 2017) - Verganti, S.; Berlato, D.; Blackwood, L.; Amores‐Fuster, I.; Polton, G. A.; Elders, R.; Doyle, R.; Taylor, A.; Murphy, S.
Abstract : Objectives: Oral malignant melanomas carry a poor‐to‐guarded prognosis because of their local invasiveness and high metastatic propensity. The Oncept melanoma vaccine is licensed to treat dogs with stage II or III locally‐controlled oral malignant melanoma and this retrospective study aimed to assess survival of affected dogs treated with the vaccine in the UK. Material and Methods: Medical records of dogs with histopathologically‐confirmed oral malignant melanoma that received the vaccine as part of their treatment were evaluated. Survival analyses for potential prognostic factors were performed. Results: Sixty‐nine dogs were included; 56 dogs, staged I to III, and with previous locoregional therapy, had a median survival time of 455 days (95% CI: 324 to 586 days). Based on Kaplan‐Meier survival analysis with associated log‐rank testing, no significant prognostic factors were identified for this population. Of the 13 patients with macroscopic disease treated with vaccine alone or in combination therapy, eight showed clinical response. Three patients with stage IV oral malignant melanoma survived 171, 178 and 288 days from diagnosis. Clinical Significance: Patients treated with the melanoma vaccine in our study had survival times similar to their counterparts receiving the vaccine in the USA. There were observed responses in patients with macroscopic disease and so the vaccine could be considered as palliative treatment in dogs with stage IV disease.